Dissecting KMT2D missense mutations in Kabuki syndrome patients. (22nd June 2018) - Cocciadiferro, Dario; Augello, Bartolomeo; De Nittis, Pasquelena; Zhang, Jiyuan; Mandriani, Barbara; Malerba, Natascia; Squeo, Gabriella M; Romano, Alessandro; Piccinni, Barbara; Verri, Tiziano; Micale, Lucia; Pasqualucci, Laura; et al.
Abstract: Kabuki syndrome is a rare autosomal dominant condition characterized by facial features, various organs malformations, postnatal growth deficiency and intellectual disability. The discovery of frequent germline mutations in the histone methyltransferase KMT2D and the demethylase KDM6A revealed a causative role for histone modifiers in this disease. However, the role of missense mutations has remained unexplored. Here, we expanded the mutation spectrum of KMT2D and KDM6A in KS by identifying 37 new KMT2D sequence variants. Moreover, we functionally dissected 14 KMT2D missense variants, by investigating their impact on the protein enzymatic activity and the binding to members of the WRAD complex. We demonstrate impaired H3K4 methyltransferase activity in 9 of the 14 mutant alleles and show that this reduced activity is due in part to disruption of protein complex formation. These findings have relevant implications for diagnostic and counseling purposes in this disease.